Placenta accreta spectrum: pathophysiology and evidence-based anatomy for prenatal ultrasound imaging. - Jauniaux, E; Collins, S; Burton, G (Elsevier, 2017)
Placenta accreta spectrum is a complex obstetric complication associated with high maternal morbidity. It is a relatively new disorder of placentation, and is the consequence of damage to the endometrium-myometrial interface of the uterine wall. When first described 80 years ago, it mainly occurred after manual removal of the placenta, uterine curettage, or endometritis. Superficial damage leads primarily to an abnormally adherent placenta, and is diagnosed as the complete or partial absence of the decidua on histology. Today, the main cause of placenta accreta spectrum is uterine surgery and, in particular, uterine scar secondary to cesarean delivery. In the absence of endometrial reepithelialization of the scar area the trophoblast and villous tissue can invade deeply within the myometrium, including its circulation, and reach the surrounding pelvic organs. The cellular changes in the trophoblast observed in placenta accreta spectrum are probably secondary to the unusual myometrial environment in which it develops, and not a primary defect of trophoblast biology leading to excessive invasion of the myometrium. Placenta accreta spectrum was separated by pathologists into 3 categories: placenta creta when the villi simply adhere to the myometrium, placenta increta when the villi invade the myometrium, and placenta percreta where the villi invade the full thickness of the myometrium. Several prenatal ultrasound signs of placenta accreta spectrum were reported over the last 35 years, principally the disappearance of the normal uteroplacental interface (clear zone), extreme thinning of the underlying myometrium, and vascular changes within the placenta (lacunae) and placental bed (hypervascularity). The pathophysiological basis of these signs is due to permanent damage of the uterine wall as far as the serosa, with placental tissue reaching the deep uterine circulation. Adherent and invasive placentation may coexist in the same placental bed and evolve with advancing gestation. This may explain why no single, or set combination of, ultrasound sign(s) was found to be specific for the depth of abnormal placentation, and accurate for the differential diagnosis between adherent and invasive placentation. Correlation of pathological and clinical findings with prenatal imaging is essential to improve screening, diagnosis, and management of placenta accreta spectrum, and standardized protocols need to be developed.